A miniaturised image based fluorescence detection system for point-of-care-testing of cocaine abuse. (16th July 2015) - Walczak, Rafał; Krüger, Jan; Moynihan, Shane
Abstract: In this paper, we describe a miniaturised image-based fluorescence detection system and demonstrate its viability as a highly sensitive tool for point-of-care-analysis of drugs of abuse in human sweat with a focus on monitor individuals for drugs of abuse. Investigations of miniaturised and low power optoelectronic configurations and methodologies for real-time image analysis were successfully carried out. The miniaturised fluorescence detection system was validated against a reference detection system under controlled laboratory conditions by analysing spiked sweat samples in dip stick and then strip with sample pad. As a result of the validation studies, a 1 ng mL −1 limit of detection of cocaine in sweat and full agreement of test results with the reference detection system can be reported. Results of the investigations open the way towards a detection system that integrates a hand-held fluorescence reader and a wearable skinpatch, and which can collect and in situ analyse sweat for the presence of cocaine at any point for up to tenths hours.